Integrating communication media in qur’anic learning: The role of flip charts in wafa-based tahsin education - Surono, Jovinka Afrina Angelly (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The Qur'an, as the holy book of Islam, serves as a guide for human life, containing commands, prohibitions, and regulations in accordance with Islamic law. Proper pronunciation, adhering to the rules of tajweed and makhraj, is essential in reading the Qur'an, particularly in the learning of Tahsin Al-Qur'an. This study aims to explore the implementation of flip chart media in Wafa-based Tahsin Al-Qur'an learning. The Wafa method, which utilizes the right brain, the chosen research site. Methods: This study is a field research employing a qualitative approach. Data collection methods include observation, interviews, and documentation. The subjects of this research are the school principal, the head of Tahsin, teachers, and students. The object of the study is the implementation of flip chart media in Wafa-based Tahsin Al-Qur'an learning. Findings: The study reveals that the implementation of flip chart media in Wafa-based Tahsin Al-Qur'an learning is conducted through structured steps, 1) opening, which includes an opening greeting, prayer, and ice-breaking activities; 2) core activities, featuring learning models such as read imitate, read listen private, and read listen classical, using flip charts as learning media; 3) closing, which includes a closing prayer. Conclusion: The study concludes that the structured use of flip chart media enhances the learning process of Tahsin Al-Qur'an in a Wafa-based approach, emphasizing the importance of structured learning steps. Novelty/Originality of this article: This research introduces the innovative use of flip chart media in Wafa-based Tahsin Al-Qur'an learning, highlighting a unique approach that combines traditional Islamic education with modern educational media.